On the long-term stability of Pd-membranes with TiO2 intermediate layers for H2 purification. (8th March 2022) - Sanz-Villanueva, D.; Alique, D.; Vizcaíno, A.J.; Calles, J.A.; Sanz, R.
Abstract: This work addresses the use of TiO2 -based particles as an intermediate layer for reaching fully dense Pd-membranes by Electroless Pore-Plating for long-time hydrogen separation. Two different intermediate layers formed by raw and Pd-doped TiO2 particles were considered. The estimated Pd-thickness of the composite membrane was reduced in half when the ceramic particles were doped with Pd nuclei before their incorporation onto the porous support by vacuum-assisted dip-coating. The real thickness of the top Pd-film was even lower (around 3 μm), as evidenced by the cross-section SEM images. However, a certain amount of palladium penetrates in some points of the porous structure of the support up to 50 μm in depth. In this manner, despite saving a noticeable amount of palladium during the membrane fabrication, lower H2 -permeance was found while permeating pure hydrogen from the inner to the outer surface of the membrane at 400 °C (3.55·10 −4 against 4.59·10 −4 mol m −2 s −1 Pa −0.5 ). Certain concentration-polarization was found in the case of feeding binary H2 –N2 mixtures for all the conditions, especially in the case of reaching the porous support before the Pd-film during the permeation process. Similarly, the effect of using sweep gas is more significant when applied on the side where the Pd-film is placed. Besides, both membranes showed good mechanical stability for around 200 h, obtaining a complete H2 /N2 ideal separation factor for the entire set of experiments. At this point, this value decreased up to around 400 for the membrane prepared with raw TiO2 particles as intermediate layer (TiO2 /Pd). At the same time, complete selectivity was maintained up to 1000 h in case of using doped TiO2 particles (Pd–TiO2 /Pd). However, a specific decrease in the H2 -permeate flux was found while operating at 450 °C due to a possible alloy between palladium and titanium that is not formed at a lower temperature (400 °C). Therefore, Pd–TiO2 /Pd membranes prepared by Electroless Pore-Plating could be very attractive to be used under stable operation in either independent separators or membrane reactors in which moderate temperatures are required. Highlights: Pd-doped titania highly reduces the Pd-thickness for reaching fully dense membranes. TiO2 barriers yield H2 permeance up to 4.17·10 −4 mol/s m 2 Pa 0.5 and complete αH2/N2 . Pd-doped titania allows stability for long-time operation up to 1000 h at 400 °C. Temperature above 450 °C leads to certain PdTi alloy and H2 permeance decrease.